An Application Of The Sidek Module Development In REBT Counseling Intervention Module Design For Orphans - Madihie, Amalia; Mohd Noah, Sidek (2012)
In Malaysia, counseling intervention module is applied as one of the tools in helping clients in counseling sessions, especially in psycho-educational groups. Therefore, it is crucial to employ a comprehensive and systematic module development model as a guideline so that a quality, reliable, and valid counseling module can be produced and developed. For instance, Sidek’s Module Development Model (SMDM) provides an alternative and integration model to develop counseling intervention module. The framework is appropriate and applicable for counselor to develop specific module for changing or modifying unwanted behaviors, especially at the early stage. A proper counseling intervention module with correct purpose of each module intervention with the purpose of to explore, intervene, investigate, and assess behaviors. SMDM is systematic and more comprehensive in developing module. The model approach has two different stages with its own purpose where a theory behind of each module is emphasized before developing any counseling module interventions. The main objective of this article is to develop a REBT counseling module focuses on self-concept development among orphans. In module developing stage, Rational Emotive Behavior Therapy approach is chosen as a theoretical background. The REBT module focused on the orphans’ self-concept in Malaysia has been validated by five experts in counseling field where .80 was obtained. A group of orphans from aged 13 to 17 years has been piloted to check the module’s reliability. As a result, Cronbach alpha .93 was obtained. Recommendation and future research as well are discussed so that more valuable, beneficial, and comprehensive counseling module intervention can be applied by other counselors or group practitioners – especially in Malaysia- with their clients according to their problems.